The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1302/0301-620x.90b5.19937
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of bilateral hip and knee ankylosis to total joint replacements

Abstract: We present a 25-year-old patient with juvenile rheumatoid arthritis and ankylosis of both hips and both knees treated by staged bilateral hip and knee arthroplasty. She was followed up for 18 months. We discuss the pre-operative planning, surgical details and post-operative rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Another case was reported in 2008: a 25-year-old female with severe ankylosis of her hips and knees secondary to rheumatoid arthritis, and her function was severely limited. She underwent staged bilateral THR, followed by a staged bilateral TKR, the functional outcome was excellent in that case as well 7 .…”
Section: Discussionmentioning
confidence: 81%
“…Another case was reported in 2008: a 25-year-old female with severe ankylosis of her hips and knees secondary to rheumatoid arthritis, and her function was severely limited. She underwent staged bilateral THR, followed by a staged bilateral TKR, the functional outcome was excellent in that case as well 7 .…”
Section: Discussionmentioning
confidence: 81%
“…According to the literature, arthritic changes become evident on average after 2-to 3 decades after hip fusion. 3,8,9 Conversion from fusion to hip replacement alone may relieve some stress put on the knee joint and consecutively-the pain, at least to some extent. Nonetheless, it is not curative, as it is unlikely it will influence the natural progression of the degenerative changes in the knee joint.…”
Section: Discussionmentioning
confidence: 99%
“…rheumatoid arthritis or juvenile arthritis), infectious or septic arthritis, or trauma (such as a proximal femoral fracture). [2][3][4] Some patients do adapt to a lack of motion of the hip joint and may report optimal function for a long period -however, it is not without compromises. Many of them face significant limitations in activities of daily living, such as putting on shoes, climbing stairs, and driving a car, and report that their condition also affects their sexual life -all of which contribute to a generally lower quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karva et al [7] reported the case of a 25-year-old patient with juvenile rheumatoid arthritis and ankylosis of both hips and both knees treated by staged bilateral hip and knee arthroplasty over 6 months. At 18 months follow up, the ranges of movement achieved at the hip and knee were comparable to those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%